2016
DOI: 10.1017/s1751731116000732
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the amino acid digestibility of oilseed meal in growing pigs

Abstract: Oilseed meal is an important source of essential amino acids (EAA) for livestock production. It is the second most important ingredient in pig feed after grains. Optimal use of these ingredients requires precise knowledge of amino acid standardized ileal digestibility (SID), which may vary depending on several factors including botanical variety or processing treatments. A metaanalysis was performed in order to derive models for predicting the SID of soybean, cotton and rapeseed meal EAA, based on chemical com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…However, researchers and feed formulators have tried to find alternative feed ingredients to replace SBM due to its relatively high price [2]. Many plant protein sources produced from oil-extraction and distillation processes have been considered as alternative feed ingredients because crude protein (CP) and AA contents in grains, oilseeds, or fruit byproducts were concentrated after processing [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, researchers and feed formulators have tried to find alternative feed ingredients to replace SBM due to its relatively high price [2]. Many plant protein sources produced from oil-extraction and distillation processes have been considered as alternative feed ingredients because crude protein (CP) and AA contents in grains, oilseeds, or fruit byproducts were concentrated after processing [3].…”
Section: Introductionmentioning
confidence: 99%
“…(2018) found that cottonseed co-products treated using a range of different processing technologies also resulted in widely varying AID. In addition, using a meta-analysis approach, Messad et al. (2016) found that the AID of amino acids in oilseeds was inversely related to their neutral detergent fibre content and that this is partially related to increased endogenous losses of amino acids (Stein et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…(1995) found that digestible energy of lupins was higher when they were fed in a wheat-based diet compared to a sugar-based diet; it was suggested that the higher digestibility when pigs were fed the wheat-based diet may have been due to more of the complex carbohydrates passing to the hindgut and providing increased substrate for hindgut fermentation. Thus, carbohydrates and fibre present in the basal diet may substantially influence the AID of amino acids (Messad et al., 2016). Therefore, the present study was conducted to determine AID of N and amino acids in pigs fed cottonseed meal (CSM) or soya bean meal (SBM) in a simple (sugar + starch) and a complex (wheat) carbohydrate-based diet.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the report of Son et al (2019) found that perilla meal contained leucine (2.25%), lysine (0.44%), and methionine (0.35%). However, the variation of AA among oilseeds may vary depending on several factors such as botanical varieties, geographical locations, climate, cultivation and processing treatment (Messad et al, 2016). Longvah and Deosthale (1998) reported that lysine of perilla seed cultivated in India was 37.13 mg/g (3.71%) and methionine 26.02 mg/g (2.60%), while perilla seed was cultivated in Fukushima, Japan was 5.2% lysine (Oita et al, 2008).…”
Section: Discussionmentioning
confidence: 99%